1996
DOI: 10.1177/44.9.8773562
|View full text |Cite
|
Sign up to set email alerts
|

Transient accumulation of perisinusoidal chondroitin sulfate proteoglycans during liver regeneration and development.

Abstract: After partial hepatectomy, the liver is capable of complete restoration of normal hepatic size, architecture, and function (regeneration). To study roles of the extracellular matrix in regeneration, the temporal and spatial sequences of deposition of several components, including collagen I, 111, and IV, fibronectin, laminin, hepacan sulfate proteoglycan (perlecan), and chondroitin sulfate proteoglycans were characterized by light microscopic immunohistochemistry in rat liver after 70% partial hepatectomy. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Contrary to the above-mentioned proteoglycans, fibroglycan expression dropped after partial hepatectomy, reaching a constant minimum level over time [86]. In another report, condroitin sulphate deposition was also detected within a few hours, reaching a peak level in regenerating tissue at 24 h after hepatectomy, followed by a gradual declination [87]. Increased collagen synthesis combined with reduced activity of cathepsin L, which generates endostatin by clivating collagens (such as collagen XVIII), were observed in rat livers within 7 days of hepatectomy [88,89].…”
Section: Proteoglycans and Liver Regenerationmentioning
confidence: 86%
See 1 more Smart Citation
“…Contrary to the above-mentioned proteoglycans, fibroglycan expression dropped after partial hepatectomy, reaching a constant minimum level over time [86]. In another report, condroitin sulphate deposition was also detected within a few hours, reaching a peak level in regenerating tissue at 24 h after hepatectomy, followed by a gradual declination [87]. Increased collagen synthesis combined with reduced activity of cathepsin L, which generates endostatin by clivating collagens (such as collagen XVIII), were observed in rat livers within 7 days of hepatectomy [88,89].…”
Section: Proteoglycans and Liver Regenerationmentioning
confidence: 86%
“…In a 1996 study, Yada et al reported changes in the pattern of expression of ECM components in hepatic tissue during rat liver regeneration after partial hepatectomy. In the regenerative phase, starting 24 h after partial hepatectomy, type I and III collagen displayed a more marked and continuous accumulation pattern throughout the hepatic lobule, while antibodies against type IV collagen, fibronectin, and perlecan yielded stronger immunoreactivity in sinusoid regions, compared to sham operated controls [87].…”
Section: Proteoglycans and Liver Regenerationmentioning
confidence: 93%